Development of Global Warming E-Module Integrated with PBL Model and Ethnoscience to Promote Students’ Environmental Literacy - Mutiara Nurul Fitri; Asrizal; Rose Amnah; Hidayati; Emiliannur; Helma (Postgraduate, University of Mataram, 2024)
Information and communication technology (ICT) in the 21st century is experiencing rapid development in the field of education. Education in the 21st century requires students to master 21st century skills and themes. One of the themes that students must master is environmental literacy. Based on the initial study conducted, students' environmental literacy is still low. One of the solutions provided to support the improvement of environmental literacy is the development of global warming e-module integrated with problem based learning model and ethnoscience to promote students' environmental literacy. The purpose of the study was to investigate the validity and practicality of the e-module. Product development refers to the Hannafin and Peck research and development model. The technique used in data analysis is descriptive statistics. Based on data analysis, two research results were obtained. First, the validity test results were 91.8 with a very good category. Second, the results of practicality according to teachers and students are 95.7 and 85.2 in the excellent category. The results concluded that the global warming e-module integrated with PBL model and ethnoscience to promote students' environmental literacy is valid and practical and can be used in supporting the physics learning process.